Phytochemical Analysis and Antibacterial Effects of Anastatica hierochuntica Extracts on Foodborne and Clinical Pathogens - Amina Omodolapo Badmos; Hanahu Onikola; Sekinat Onigbinde; Rasaq Onikola (Turkish Journal of Agriculture: Food Science and Technology)
This study explores the phytochemical composition and antibacterial properties of aqueous and methanolic extracts of Anastatica hierochuntica against foodborne pathogens and clinical isolates. Phytochemical analysis identified key compounds, including alkaloids (7.15 ± 0.0365 mg/g), flavonoids (3.16 ± 0.007 mg/g), and tannins (0.18 ± 0.0025 mg/g). Food samples yielded Escherichia coli isolates, Staphylococcus aureus, Staphylococcus epidermidis, Salmonella typhi, and Serratia marcescens. The antibacterial efficacy was assessed using the agar well diffusion method against these pathogens and clinical isolates, including Pseudomonas aeruginosa and Klebsiella pneumoniae. The aqueous extract demonstrated strong antibacterial activity against all food pathogens, with Staphylococcus aureus, Salmonella typhi, and Serratia marcescens exhibiting the largest inhibitory zones (34 mm). Among clinical isolates, only Klebsiella pneumoniae and Pseudomonas aeruginosa showed selective inhibition. Conversely, the methanolic extract was largely ineffective, displaying activity only against Serratia marcescens (average inhibitory zone of 11.7 mm). These results underscore the potential of A. hierochuntica aqueous extracts as a natural antimicrobial agent and suggest further investigation into its bioactive compounds for improving food safety and addressing multidrug-resistant pathogens.